Challenges faced by edentulous patients (EDPs) during complete denture prostheses (CDP) service delivery in Fiji - a qualitative study - Meenal Nand; Masoud Mohammadnezhad (BMC, 2022)
Abstract Background Edentulism is a state of having no teeth in the oral cavity, an irreversible condition popularly known as the marker of disease burden on the oral health. For edentulous patients (EDPs) Complete Denture Prostheses (CDP) is a means to improve oral health. Due to limited studies in this area, this research aimed to explore the challenges faced by the EDPs during CDP service delivery in Fiji. Methods A directed descriptive qualitative study was conducted among EDPs attending Dental Prosthetic Clinics (DPCs) at the four centres in Fiji under purposive sampling. A semi-structured questionnaire with open ended questions was used for in-depth interview with EDPs who had worn CDP for 1 year via telephone. Participant responses were recorded, transcribed verbatim and analyzed manually using thematic analysis. Results A total of 30 EDPs participated in the study. Six themes were identified as challenges faced by the EDPs during CDP service delivery in Fiji: lack of information, non-compliance, overwhelmed by illness, reduction on quality of life (QoL) financial barriers to CDP treatment care and personal acceptance. 77% of EDPs felt they did not receive adequate information on CDP when attending DPCs which indicated the non-compliance nature irrespective of using and cleaning CDP on a daily basis. The Dental Professionals (DPs) at the DPCs gave their full support in attending to the CDP challenges faced by the EDPs in Fiji during the review clinics. Conclusion The EDPs expressed a variety of challenges that was faced while seeking appropriate CDP services in Fiji. The findings demonstrate the need to explore approaches to develop patients' engagement practices during CDP service delivery by the Dental professionals (DPs), which leads to effective oral health promotion in Fiji for CDP wearers.